Mobile architecture - Seonwook, Kim.; Pyo, Mi Young. (Construction and design manual., 2012)
There never was a time when there was not motion, and never will be a time when there will not be motion. Aristotle Mobility is a challenge that architecture has always had to confront; Aristotle was merely the first to philosophize about it. In the present age of digital nomadism, the art of building, with its traditional focus on immobility in fixed places, finds itself confronted by the temptation to relinquish its characteristic rootedness and to abandon itself to the irresistible pull of mobility. In countless manifestos, avant-garde architects describe how they intend to dissolve buildings and indeed whole cities, create an architecture based on a machine aesthetic that prominently involves mobility, and give their buildings legs or wheels.Notwithstanding the many prophets of doom that see solid, sedentary architecture sacrificed to mobile lifestyles, architects continue to take up the challenge and design portable houses. The results are often both practical and innovative, as is demonstrated on the more than 800 pages of this new title in the Construction and Design Manual series, in which 43 international design teams present works ranging from architectural follies to handicapped accessible furnishings and life-saving shelters.